PERANCANGAN SISTEM INFORMASI DAN SHODAQOH ONLINE DI MASJID JAMI AL-HUDA BERBASIS WEB MENGGUNAKAN METODE WATERFALL - Sinta Rahmawati; Achmad Lutfi Fuadi (CV SWA Anugerah, 2024)
Jami Al-Huda Mosque is one of the mosques that is quite crowded with Muslims. As an important place of worship, the mosque requires effective and efficient management of activities and information. Currently, the management of alms in the mosque is still done manually, causing several obstacles such as difficulties in recording, reporting, and managing alms funds as a whole. This study aims to design and implement an online information and alms system at the Jami Al-Huda Mosque based on the web using the waterfall method . This system is designed with the aim of simplifying the process of collecting and managing alms and increasing efficiency in providing information to the congregation. The waterfall method was chosen as an approach in system development to ensure structured and sequential stages. This study began by analyzing system needs and designing the system structure in detail. Furthermore, the system was implemented using web technology and tested to ensure good performance. The results of this study are an online information and alms system that can be accessed via the web, allowing the congregation to make donations online and monitor the progress of alms collection. Keywords : Information System, Online Shodaqoh , Mosque, Web, Waterfall Method